1979
DOI: 10.1029/ja084ia03p00823
|View full text |Cite
|
Sign up to set email alerts
|

Auroral O(¹S) production and loss processes: Ground‐based measurements of the artificial auroral experiment precede

Abstract: An artificial auroral experiment, Precede, was performed in the 80-to 120-km altitude range above the White Sands Missile Range, New Mexico, in October 1974. A 2-kW rocket-borne electron accelerator, square wave modulated at 0.5 Hz, was activated at 95 km on payload ascent, was pulsed continuously through apogee (120 km) to a descent altitude of approximately 80 km, and provided a total of 90 pulses of a 2.5-kV 0.8-A electron beam over a period of 180 s. A ground-based dual channel telephotometer recorded the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The combination of almost 30 frames with background removed produces a very high signal to noise ratio (~30 to 1). For comparison, previous rocket experiments of artificial aurora had signal to noise ratios of only -4 to 1 [e.g., O'Neil et al, 1979]. Figure 2 shows one of these composite images in a three-dimensional perspective plot.…”
Section: Shape Of the Auroral Patch In White Lightmentioning
confidence: 99%
“…The combination of almost 30 frames with background removed produces a very high signal to noise ratio (~30 to 1). For comparison, previous rocket experiments of artificial aurora had signal to noise ratios of only -4 to 1 [e.g., O'Neil et al, 1979]. Figure 2 shows one of these composite images in a three-dimensional perspective plot.…”
Section: Shape Of the Auroral Patch In White Lightmentioning
confidence: 99%
“…Artificial auroral experiments had been conducted previously from sounding rockets [Hess et al, 1971;Davis et al, 1971Davis et al, , 1980O'Neil et al, 1979]. See also the comprehensive review by Winckler [1980].…”
Section: The Space Experiments With Particle Acceleratorsmentioning
confidence: 99%
“…This problem has received recent attention following the laboratory work of Zipf (1980b) who concluded that his earlier (1970) measurement of a high yield of O(~S) at about 0.1 was produced by a source population of vibrationally excited + 2 02 (rig) and that yields from the lowest vibrational levels of the ground state ion were considerably less, near 0.02. The variety of yields calculated by aeronomical studies (Hernandez, 1971 ;Hays and Sharp, 1973;Frederick et al, 1976;Kopp et al, 1977b;O'Neil et al, 1979) could then be attributed to variations in the amount of vibrational development of the recombining O~*. Theoretical calculations of potential energy curves (Michels, 1979;Guberman, 1979) support this contention, but Bates and Zipf (1981) subsequently found that vibrational deactivation by atomic oxygen would proceed too rapidly to allow recombination to occur except in the lowest vibrational states, and suggested an electron temperature dependence of the O(~S) yield instead.…”
Section: Auroral Transition Of Oi 5577mentioning
confidence: 99%